Computer-Linked Memorandum of Pathology System (CLIMPS 7909) for Interactive Storage and Analysis of Surgical Pathology Data - Takahashi, M.; Masuda, M.; Isiglo, K.; Matsumoto, T. (Methods of Information in Medicine, 1980)
A new interactive data base management system for surgical pathology is described which was developed by modification of the previously reported system for autopsy records [23]. As the name implies, it serves as a personal memorandum. Always led by the computer, it is easy to write and read, whenever necessary, without knowledge of programming or data format. The outstanding features are its flexibility of operation and the on-line availability of simple statistical data on some items (diagnoses, topography, histology, age and sex) in response to the specification of search condition so that it provides an opportunity to expand association of ideas during the process of diagnosis and serves as a diagnostic support system. The CLIMPS has been successfully tested with over 770 surgical pathology records. Some problems to be expected in the future are discussed.
Keywords: CLIMPS; Surgical Pathology; Interactive Data Management; On-line Statistics; Diagnostic Aid; Computer-assisted Instruction; SNOP Code